CONTRIBUTION OF ISLAMIC CIVILIZATION TO THE WESTERN CIVILIZATION (HISTORICAL REVIEW) - Hamzah, Ekawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract: This paper aims to reveal the contribution of Islamic civilization to western civilization by discussing: (1) The early history of Islamic civilization (2) The entry path of Islamic civilization to the West. The results of this study reveal that Islamic civilization entered the west, precisely in Europe in three ways, namely the channel of Islamic civilization which influenced Europe through Spain, Sicily, and the Crusade. In this route trade exchange took place, but the most important channel in this case was Islamic Spain. Spain is the most important place for the West to absorb Islamic civilization, both in political, social, economic and civilizational relations between countries. That is a fact of Spanish history for more than seven centuries under Islamic rule. Western civilization was built from the womb of the early phase of Islamic history in occupying Spain. Socio-politically, Islam is in a very strong position to expand and civilizationally is in its golden peak. This expansion process was followed by the transfer of science from the Muslims to the Spanish population at that time. The open culture and the generosity of knowledge built by the Muslims at that time made every group, region, or ethnic group very wide open to gain knowledge from Muslim scholars, including many Europeans who studied in various fields, both science and technology. 'aqli science and naqli science. After they returned to their respective areas, many developed this knowledge in mainland Europe.